PENGEMBANGAN MEDIA PEMBELAJARAN POSTER PADA SUB MATERI MASA KEKUASAAN VOC KELAS XI SMA NEGERI 2 PONTIANAK - Mulia Agustiyani; F.Y. Khosmas; Ika Rahmatika Chalimi (Universitas Tanjungpura, 2020)
AbstractThis study aims to determine the stages of development and the advisability of developing poster products in the sub-material period of the VOC class XI of SMA Negeri 2 Pontianak from material and media expertsas well as responses from students. The research method used without is the product development method (research and development) with the Borg and Gall research model and has been modified. Data validation media sources were material experts and media experts, while data sources for small-scale and large-scale trials are class XI students of SMA Negeri 2 Pontianak. The collecting data used expert judgment questionnaires and student questionnaire responses. The results of the validation of the material expert showsan average value of 86% and for the validation of the media experts obtained an average value of 97%. The results of the validation of the experts shows that the poster development product is worthy without revision with very good information. Whereas the results of small-scale trials obtain an average value of 81.7% and the average value for the results of large-scale trials was 81.2%. From all the results of the study shows that the product development of this poster received a positive response from the respondents. It can be concluded from the results of this study that poster development products are suitable for use in teaching and learning in the classroom.Keywords: Development, Learning Media, Poster